2018
DOI: 10.1016/j.ceca.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

ORAI channels and cancer

Abstract: Cancer is a major cause of death. The diversity of cancer types and the propensity of cancers to acquire resistance to therapies, including new molecularly targeted and immune-based therapies, drives the search for new ways to understand cancer progression. The remodelling of calcium (Ca) signalling and the role of the Ca signal in controlling key events in cancer cells such as proliferation, invasion and the acquisition of resistance to cell death pathways is well established. Most of the work defining such c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 85 publications
(147 reference statements)
1
51
0
6
Order By: Relevance
“…SOCE is the most ubiquitous pathway for Ca 2+ transport from the extracellular space and activated following the depletion of Ca 2+ stores from the ER. Recently, SOCE has emerged as critical machinery for Ca 2+ influx, contributing to various malignant phenotypes in cancer cells [44][45][46]. SOCE is also shown to be responsible for cisplatin-induced apoptosis [20].…”
Section: Strikingly Dats Seems To Evoke Ca 2+mentioning
confidence: 99%
“…SOCE is the most ubiquitous pathway for Ca 2+ transport from the extracellular space and activated following the depletion of Ca 2+ stores from the ER. Recently, SOCE has emerged as critical machinery for Ca 2+ influx, contributing to various malignant phenotypes in cancer cells [44][45][46]. SOCE is also shown to be responsible for cisplatin-induced apoptosis [20].…”
Section: Strikingly Dats Seems To Evoke Ca 2+mentioning
confidence: 99%
“…This contrasts, however, with the ubiquitous expression of ORAI and STIM genes in many other tissues and the presence of SOCE in many cell types in humans, mice and other species. Furthermore, studies of mice with genetic deletion of Orai and Stim genes have revealed additional roles of CRAC channels in health and disease that go beyond the phenotype of patients with CRAC channelopathy and that are the topic of a second group of reviews in this special issue [20][21][22][23][24][25]. Arguably the most dramatic difference between CRAC channel deficient patients and mice is that Orai1 -/or Stim1 -/mice are not viable, which is most apparent on the inbred C57BL/6 background.…”
mentioning
confidence: 99%
“…Over the last 10 years, many labs have investigated the role of SOCE in cancer growth, proliferation and metastasis. Chalmers & Monteith review the current literature on Ca 2+ signals in cancer and how they control the properties of cancer cells including their proliferation, invasion and resistance to cell death [20]. Whereas much earlier work on Ca 2+ signaling in cancer had focused on transient receptor potential (TRP) channels, the discovery of ORAI and STIM genes has attracted considerable interest in SOCE as a pathway deregulated in tumor cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, its cellular level is always subjected to tight regulations, mainly by the activity of three plasma membrane Ca 2+ channels, voltage-gated Ca 2+ channels, Orai-mediated store-operated channels, and transient receptor potential-mediated Ca 2+ channels. It has been revealed that disruption in the expression or function of these channels is often correlated with carcinogenesis and/or chemoresistance [119,120]. Hence, targeting their expression level or function may serve as an effective strategy to improve cancer treatment.…”
Section: Ca 2+ Channelsmentioning
confidence: 99%